Cooperation Based on The Mudharabah bil Mukhabarah Contract as an Effort to Maintain Food Security - Susanti, Dyah Ochtorina; Sari, Nuzulia Kumala; Adonara, Firman Floranta; Tektoka, Rahmadi Indra; Putri, Auliya Safira (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
The issue of food security in Indonesia through the Department of Agriculture has been designated as a policy priority in agricultural development. This is due to the lack of adequate food availability for the community as shown d by the continued import of staple food ingredients from other countries, especially rice that is the main food source for the Indonesian people. The price of rice is increasing due to the decline in rice harvest area and also driven by the impact of El Nino, so that efforts are needed to maintain food security. This research is based on the concept of mudharabah bil mukhabarah which combines the rules of Islamic law and positive law in Indonesia that are applied to agricultural cooperation as an effort to maintain food security. The research method used in this research is a normative legal research type with a statutory and conceptual approach. The results of the research are that cooperation based on a mudharabah bil mukhabarah agreement combines three parties, namely (1) the Government (BULOG) as a provider of capital in the form of fertilizer, superior plant seeds and agricultural equipment, (2) the land owner who provides agricultural land, and ( 3) Cultivator farmers who manage agricultural land using the expertise, energy and time they have. The harvest results in this collaboration are sold back to BULOG and the profits are distributed to the parties according to the ratio agreed at the beginning of the agreement, so that food supplies can be met with fairness, transparency and sustainability in every transaction and relationship between the parties in maintaining national food security.